Elevated Mhp462 antibody induced by natural infection but not in vitro culture of Mycoplasma hyopneumoniae. Issue 8 (August 2020) - Ning, Yaru; Zhou, Yaoqin; Wang, Zhaodi; Wen, Yukang; Xu, Zuobo; Tian, Yaqin; Yang, Mei; Wang, Xudong; Yang, Yujiao; Ding, Honglei
Abstract: Mycoplasma hyopneumoniae is the respiratory pathogen of porcine enzootic pneumonia, a chronic respiratory infectious disease that causes substantial pecuniary losses to pig husbandry worldwide. Commercial bacterins only provide incomplete protection and do not prevent the colonization and transmission of M. hyopneumoniae . Identification of new protective antigens is a key imperative for the development of more effective novel vaccine. The objective of this study was to evaluate antibody responses of 27 recombinant proteins in convalescent sera obtained from pigs that were naturally infected with M. hyopneumoniae . Fifteen proteins were identified as serological immunodominant antigens, while 3 proteins were not recognized by any convalescent serum. Moreover, Mhp462, a leucine aminopeptidase, was found to be a discriminative serological immunodominant antigen which reacted with convalescent sera but not with hyperimmune sera. The serological immunodominant proteins were antigenic and were expressed during infection; this suggests that these proteins (especially the discriminative one) are potential candidate antigens for the development of next generation vaccines against M. hyopneumoniae . Abstract : Biotechnology; Microbiology; Infectious disease; Vaccination; Bacteria; Microbial biotechnology; Veterinary medicine; Mycoplasma hyopneumoniae, Serological immunodominant protein, Convalescent sera, Hyperimmune sera, ELISA